A qualitative study of how mental models impact engineering students' engagement with empathic communication exercises. Issue 2 (2nd July 2020) - Sochacka, Nicola W.; Youngblood, Kathryn M.; Walther, Joachim; Miller, Shari E.
ABSTRACT: Empathy is an important professional skill for engineers. Defined as the capacity to understand and share the feelings of others, empathy can help engineers work on teams and interact more effectively with clients. Approaches designed to teach empathy to engineering students, however, are limited, as are studies on such interventions. This study investigated two research questions: What mental models about engineering and engineering relationships do students bring with them into engineering classrooms? And, how do these mental models impact students' engagement with and understanding of empathic communication exercises? Data for the study included student reflections from second-year mechanical engineering students (n = 36 x 4 reflections each, one for each of the four empathic communication modules). The findings comprised five themes from a cross-section of the data at one point in the semester and narrative trajectories that capture the experiences of two students across all four modules. The findings suggest that learning about empathy in engineering can call into question the mental models students bring with them about what engineering is and what engineers do. Instructors need to be aware of the challenges associated with confronting these pre-existing understandings and attend to them in the design, implementation, and assessment of empathy-related activities.